Peran Badan Usaha Milik Desa (BUMDes) Dalam Pengelolaan Potensi Desa Untuk Meningkatkan Pendapatan Asli Desas Maju Mandiri Desa Peguyangan Kaja Denpasar): Studi Kasus BUMDes Maju Mandiri Desa Peguyangan Kaja Denpasar - Putrawan, I Komang Bayu Aditya; Sudiana, I Wayan; Yuniasih, Ni Wayan (Hita Akuntansi dan Keuangan, 2025)
This research seeks to explore the contribution of the Village-Owned Enterprise (BUMDes) Maju Mandiri in utilizing village resources and addressing business obstacles to enhance Village Original Income (PADes) in Peguyangan Kaja, Denpasar. A descriptive qualitative approach was applied, observations, documentation, and literature reviews as data collection methods. Findings reveal that BUMDes Maju Mandiri operates three core business units: trading, intermediary services (providing consumption needs for village events), and PPOB (bill payment services). These units make a considerable contribution to PADes, though they face barriers such as competition from private retailers, taxation requirements, and limited starting capital. Even with a profit decline in 2023, the enterprise consistently generated income for PAD. The study concludes that BUMDes plays a relatively effective role in boosting PADes and fostering local economic prospects. Recommendations include leveraging village assets such as Tukad Rarangan tourism and MSMEs, enhancing service quality, and strengthening both marketing and partnership strategies.